Examining the linkage and structural transformation effects of nickel industrialization: A case of South Halmahera, Indonesia - Fitrianto, Gigih; Permana, Yudistira Hendra; Sanjaya, Muhammad Ryan; Sholihin, Mahfud; Farouqi, Muhammad Akmal (Asian Journal of Economic Modelling, 2025)
The global surge in electric vehicle demand has intensified focus on green economies. Indonesia, home to the world’s largest nickel reserves, enacted a nickel ore export ban to maximize domestic value-added through downstream industrialization, notably in South Halmahera, North Maluku. We examine the effects of nickel downstream processing by estimating multiplier impacts for mining and manufacturing sectors at regional and national levels, identifying structural transformation in South Halmahera, and assessing the competitiveness relative to North Maluku Province. Several methods were used, such as the Leontief inverse matrix of updated Input–Output (IO) and Interregional Input–Output (IRIO) tables, shift-share (SS), and location quotient (LQ). We find that manufacturing multipliers have grown substantially, but with significant leakage as benefits largely flow to other provinces. SS analysis also indicates rising productivity, labor reallocation into manufacturing, and the emergence of supporting sectors. LQ results confirm a sharp, although temporary, increase in manufacturing competitiveness that also boosts mining productivity. Despite transformative effects on nickel industrialization, much of the value-added potential remains uncaptured due to weak local integration. Developing reliable supporting industries is crucial to attaining economic diversification for long-term sustainable growth, considering the limited amount of nickel reserves.